PERJALANAN KARIR GURU DALAM PERSPEKTIF MANAJEMEN KEPALA MADRASAH DI MTs WAHID HASYIM BATANG - Failasuf Fadli (STKIP Pesisir Selatan, 2019)
Teachers are human resources who become planners, actors and determinants of achieving organizational goals. The existence of teachers is very important for the continuity of an educational institution, but there are still educational institutions that ignore the process of teacher recruitment, which sometimes seems careless, then the school in fostering teachers is also lacking due to lack of budget. the purpose of this study is to explore the process of procurement of teachers, to uncover the process of placement of teachers, to explain the process of teacher development, to find the process of providing compensation to teachers, and explain the process of dismissing teachers. The approach used in this research method is a qualitative approach. The type of this research is field research with primary research data sources are the head of the madrasa, management of the foundation, and teachers while the secondary data sources are administrative staff, and students. By using data collection methods namely; interview, observation and documentation. While for the data analysis method is to use inductive analysis. This study resulted in the teacher's career journey at MTs Wahid Hasyim from the start of recruitment to dismissal not yet well implemented. Recruitment system. From these results it can be concluded that the principal has an important role in managing the career of the teacher, so that the teachers at MTs Wahid Hasyim are qualified and have good competence